Influence of ventilation in EDPE bags on shelf-life of Indian gooseberry (Emblica officinalis ) - PANDEY, G; SINGH, B P; PANDEY, M K; SAROLIA, D K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was undertaken during the year 2003-04 in LDPE film bags of 200 gauge thickness provided with 2 and 2.5% ventilation to study the influence of modified atmospheric packaging on shelf-life of ’Chakaiya’ Indian gooseberry (E?nhlica officitznlis Gaertn) along with control as brown paper bags under ambient condition (18 12’C and 85 13% relative humidity). In general, increase in cumulative physiological loss in weight, yellowness index, total soluble solids, acidity, tannin and decrease in ascorbic acid contents were observed among treatments with advancement of storage period. Packaging of fruits in low density polyethylene (LDPE) film bags with 2% ventilation exhibited minimum per cent comulative physiological loss in weight (12.47%) and yellowness index (YI=70.65) with more vitamin C retention and marketable fruits up to 15 days of storage while control fruits desiccated, developed brown patches on fruit skin resulted in poor quality and marketability, exhibiting 4-6 days of storage life. Thus, it concluded that 2% ventilated LDPE film bags of 200 gauge thickness is best packaging for prolonging the shelf-life.